rdlc 2020
DOI: 10.7764/rdlc.19.1.127-133
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of resistance of sodium meta silicate activated slag mortar to acidic and basic mediums

Abstract: This study presents the resistance of sodium meta-silicate activated ground granulated blast furnace slag (GGBFS) to acidic and basic mediums. Geopolymer mortars were prepared with GGBFS activated by sodium meta-silicate activator having 4, 8, and 12% sodium concentrations by mass of slag. These mortars were exposed to two types of acid solutions, H2SO4 and HCl with a 5% concentration of acid-water solution. Similarly, some specimens were exposed to a basic medium composed of 25% NaOH solution with water. Expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Bingol et al ( 2020) observed an increase in the compressive strength of water-cured slag GPM specimens when subjected to H2SO4 media. The authors utilized a sodium metasilicate activator in their investigation [83].…”
Section: Geopolymer Paste (Gpp)mentioning
confidence: 99%
“…Bingol et al ( 2020) observed an increase in the compressive strength of water-cured slag GPM specimens when subjected to H2SO4 media. The authors utilized a sodium metasilicate activator in their investigation [83].…”
Section: Geopolymer Paste (Gpp)mentioning
confidence: 99%
“…Therefore, it can be used as an alternative eco-friendly material (Luo, Xu, and Li 2015). In the production of geopolymer, industrial wastes such as FA, blast furnace slag, silica fume and natural materials such as kaolin, clay, lime and red mud are used as binders (Bingöl et al 2020;Khadka et al 2020;Li et al 2019;Qu et al 2020;Sarker 2011;Sukprasert et al 2021;Yurt 2020aYurt , 2020b. These binders are activated with various alkalis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the environmental problems of the cement sector, efforts are continuing to produce an alternative binder to cement. Industrial wastes such as blast furnace slag, fly ash, floor ash and silica fume are activated with various alkalis (Bingöl et al 2020;Şahin, Mahyar & Erdoğan 2016). As a result of this chemical activation, cement-like binder can be produced.…”
Section: Introductionmentioning
confidence: 99%